Acculturation and consumer loyalty among immigrants: a cross-national study. Issue 9 (2nd September 2014) - Segev, Sigal; Ruvio, Ayalla; Shoham, Aviv; Velan, Dalia
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the effect of acculturation on immigrant consumers' loyalty. The authors posit that the acculturation orientation of immigrants determines their consumer loyalty to both ethnic and mainstream brands and stores. Design/methodology/approach – Using a sample of Hispanic consumers in the USA and consumers from the former Soviet Union in Israel, this study tests a model in which two acculturation continua, original culture maintenance and host culture adaptation, serve as antecedents for immigrants' consumer loyalty. Findings – Acculturation determines the extent of immigrants' consumer loyalty. Both acculturation continua are associated with distinct loyalty patterns that are similar across the two immigrant groups. Research limitations/implications – Despite sampling limitations, the paper demonstrates that immigrants' acculturation orientation influences their loyalty to ethnic and mainstream brands and stores. Shared by ethnic consumers in two culturally diverse markets, this relationship transcends geographic boundaries. Practical implications – The results provide insights for marketers with respect to the development of segmentation and positioning strategies and tactical implementations that address the preferences of ethnic consumers. Social implications – This paper highlights the importance of understanding the unique needs of ethnic consumers and addressing them. Successful integration of immigrant consumers into the marketplace can also help in their integration into the host society at large. Originality/value – Findings shed light on the commonalities and differences among immigrant groups in different national settings. The paper highlights the role of cultural transition as a key experience that affects immigrants regardless of specific environmental or situational circumstances.